Teachers' perceptions of participative management in a primary school in Namibia - Kambonde, Samuel Angaleni (Rhodes University, Faculty of Education, Department of Education, 2008)
Participative management, a key theme in contemporary management literature, is one of the central aims of the decentralization policy in Namibian education. Current perceptions of participative management on the part of teachers in Namibia are therefore of topical interest. This study set out to explore such perceptions among teachers in a Namibian primary school. The study is an interpretive case study focusing on six individual teachers' understanding and experience of participative management within their place of work, a primary school in the Oshikoto region of Namibia. Semi-structured interviews, observation and document analysis were used to gather data. The study revealed a strong sense of commitment among the respondents to participative management and its accompanying practices, such as shared decision making and broad stakeholder involvement. Participative management was implemented chiefly through a committee structure for school organisation and government. Respondents also highlighted challenges facing participative management, such as the persistence of autocratic leadership, conflicts of interest in decision making, laziness and unwillingness among staff members, and a lack of understanding among parents concerning their role in the schooling of their children. HIV/AIDS was also seen to pose challenges to the free and frequent participation of stakeholders. The chief recommendation arising from these findings is that school leaders and managers' understanding of tenets of participative management, such as site-based management and democratic management approaches, requires improvement and development.
Keywords: Education, Elementary -- Namibia; Teachers -- Namibia; School management and organization -- Namibia; Educational leadership -- Namibia